Trophic Factors in Inflammation and Regeneration: The Role of MANF and CDNF - Sousa-Victor, Pedro; Jasper, Heinrich; Neves, Joana (Frontiers in Physiology, 2018)
Regeneration is an important process in multicellular organisms, responsible for homeostatic renewal and repair of different organs after injury. Immune cell activation is observed at early stages of the regenerative response and its regulation is essential for regenerative success. Thus, immune regulators play central roles in optimizing regenerative responses. Neurotrophic factors (NTFs) are secreted molecules, defined by their ability to support neuronal cell types. However, emerging evidence suggests that they can also play important functions in the regulation of immune cell activation and tissue repair. Here we discuss the literature supporting a role of NTFs in the regulation of inflammation and regeneration. We will focus, in particular, in the emerging roles of mesencephalic astrocyte-derived neurotrophic factor (MANF) and cerebral dopamine neurotrophic factor (CDNF) in the regulation of immune cell function and in the central role that immune modulation plays in their biological activity in vivo. Finally, we will discuss the potential use of these factors to optimize regenerative success in vivo, both within and beyond the nervous system.